Superior performance of rGO-tin oxide nanocomposite for selective reduction of CO2to methanol - Romeiro, F. C. [UNESP] (2021)
This study reports on the photoelectrochemical reduction of CO2 to methanol using Sn3O4 and reduced graphene oxide-tin oxide (rGO-Sn) nanocomposite synthesized through the microwave-assisted hydrothermal method. The resulting rGO-Sn nanocomposite exhibited enhanced activity and good stability during photoelectrochemical CO2 reduction explained by Z-scheme electron transport. Graphene oxide (GO) has played a crucial role in the chemical composition and morphology of nanocomposites. The interaction between GO and Sn2+ ions during synthesis promoted the formation of the SnO2 phase in the nanocomposite, thus generating mixed rGO/Sn3O4/SnO2 phases (the rGO-Sn nanocomposite). Remarkable selectivity for CO2/methanol conversion was obtained for both Sn3O4 and the nanocomposite at different potentials, in which the nanocomposite presented the highest conversion to methanol with a faradaic efficiency of 45 % at -0.3 V vs. Ag/AgCl. The improved activity of the nanocomposite was ascribed to the efficient use of solar energy (UV + visible light), to the decrease in electronic recombination in nanocomposite, which enabled an efficient electron-hole separation on the surface of the nanocomposite, and to the presence of rGO being combined with Sn3O4 and SnO2 structures, which ensured a faster charge transport rate. This study reveals the potential of rGO-Sn nanocomposites as photocathodic material for solar-to-chemical energy conversion.